Isolated fetal neural tube defects associate with increased risk of placental pathology: Evidence from the Collaborative Perinatal Project. (October 2021) - White, Marina; Grynspan, David; Van Mieghem, Tim; Connor, Kristin L.
Abstract: Introduction: Neural tube defects (NTDs) are amongst the most common congenital anomalies and are associated with significant postnatal morbidity, but also with a higher incidence of low birthweight and fetal growth restriction. Despite the placenta being a critical determinant of fetal growth, placental development has not been extensively studied in fetuses with NTDs. Methods: We performed a matched case-cohort study using data from the Collaborative Perinatal Project to assess the risk of placental pathology in pregnancies with an isolated fetal NTD (cases; n = 74) compared to those without any congenital anomalies (controls; n = 148). We hypothesised that cases would be at an increased risk of placental pathology compared to controls. Data were analysed using adjusted generalized linear and nominal logistic regression models. Results are presented as adjusted β or adjusted odds ratio (aOR; 95% confidence interval). Results: Cases had lower placental weight (β = −22.2 g [-37.8 to −6.6]), surface area (β = −9.6 cm 2 [-18.3 to −1.0]) and birth length z-scores (β = −0.4 [-0.7 to −0.001]) compared to controls. Cases were more likely to have a single umbilical artery (vs. two; 6 [8.1%] vs. 1 [0.7%]; aOR = 301 [52.6–1726]), placental hypermaturity (9 [12.2%] vs. 5 [3.4%]; aOR = 6.8 [3.1–14.7]), many (vs. few) Hofbauer cells (9 [12.2%] vs. 7 [4.7%]; aOR = 3.02 [1.2–7.3]), and stromal fibrosis (9 [12.2%] vs. 10 [6.8%]; aOR = 3.0 [1.4–6.3]) in placental terminal villi compared to controls. Conclusions: Fetuses with isolated NTDs may be at increased risk of placental pathology, which could be contributing to poor fetal growth in these pregnancies and subsequent postnatal morbidities. Highlights: Neural tube defects associate with increased risk of poor fetal growth and preterm birth. Fetuses with neural tube defects may be at increased risk of placental pathology. Placental maldevelopment may increase the risk of fetal or postnatal mortality and comorbidities.